The degree of practice educational ethics among teachers of physical education and sport )Field Study on Physical Education and Sports Teachers) - djaouadi ali,; خالد جوادي, (sports creativity, 2025)
The degree of practice educational ethics among teachers of physical education and sport Professors: Abstract: The current study aimed at identifying the degree of practice educational ethics by teachers of physical education and sport in the field of teaching from their point of view, as well as identifying differences in incentives according to the variables of experience and qualification, the study sample consisted of 55 teachers They were randomly selected, the study was based on a questionnaire prepared by the researchers consisting of 22 paragraphs including the practice educational material incentive and emotional ,the data were statistically processed using arithmetic mean, standard deviation and mono-variance analysis. The result has shown that the degree of the incentives that offered to teachers of physical education and sport was with a high extent, and the existence of differences in the degree of practice educational incentive for the experience and social status, there are no differences in the degree of incentives in terms of the scientific qualification factor. Key words : incentives ;experience; scientific qualification. social status ;teacher of physical education and sport